The Other Bolsheviks Lenin and His Critics, 1904-1914 - Williams, Robert C. (Indiana University Press, 1986)
Focusing on the thought and activities of A. A. Vogdanov, A. V. Lunacharsky, Maxim Gorky, and V. D. Bonch-Bruevich, this political and intellectual history of Bolshevism before 1914 shows that Lenin by no means dominated or controlled his own fraction of the Russian Social Democratic Worker's Party, as his famous essay What Is to Be Done? (1902) implies. Rather, Lenin and his rival, Alexander Bogdanov, struggled to persuade divided and fissiparous revolutionary exiles to accept their respective ideals of rigid party authority and Marxist orthodoxy, on the one hand, or collectivist and syndicalist manipulation of the masses, on the other.